Do evidence based interventions for chronic fatigue syndrome improve sleep? A systematic review and narrative synthesis. (June 2017) - Russell, Charlotte; Kyle, Simon D.; Wearden, Alison J.
Summary: Cognitive behavioural therapy (CBT) and graded exercise therapy (GET) are recommended evidence based treatments for chronic fatigue syndrome (CFS), with research supporting their effectiveness in reducing fatigue and functional impairment. However, little research has focussed on the effect of these treatments on sleep, despite high reported sleep disturbance in CFS. Using a narrative synthesis approach, we aimed to 1) systematically identify and summarise the current evidence for the effectiveness of CBT and GET in improving sleep; 2) consider factors influencing treatment effectiveness, including incorporation of sleep management techniques; and 3) consider the appropriateness of sleep outcome measures used within evaluations. Studies evaluating CBT and/or GET for CFS, and including a sleep outcome were eligible for inclusion. Eight studies were identified. We found that GET interventions can improve sleep but this effect is inconsistent across studies. For CBT the evidence is limited with only one of two evaluations demonstrating sleep-related improvements. We conclude from existing research that we know little about the effects of including sleep management components within CBT and GET interventions. We suggest that future research should explore the effectiveness of sleep components within interventions, and sleep specific interventions, using comprehensive outcome measures that fully capture the range of sleep difficulties experienced in CFS.